Factors influencing health care use by health insurance subscribers and medical aid beneficiaries: a study based on data from the Korea welfare panel study database - Na Young Kong; Dong Hee Kim (BMC, 2020)
Abstract Background The use of health care services is influenced by various factors, including demographic, social, economic, and health status factors. This study aimed to identify the factors that influence health care use in health insurance subscribers and medical aid beneficiaries in Korea. Methods A total of 11,793 subjects were identified, including 10,838 health insurance subscribers and 955 medical aid beneficiaries, using the Korea Welfare Panel Study database. The data were analysed by percentage, t-test, and multiple regression using SPSS 20.0. Results Medical aid beneficiaries had 13.51 more days of outpatient visits and 8.38 more days of hospitalization compared with health insurance subscribers. Factors affecting the frequency of outpatient visits for health insurance subscribers were gender, age, household type, education level, income level, administrative district, perceived health status, chronic disease, and disability. These factors accounted for 19.8% of explanation (p < .001). Whereas, gender, household type, administrative district, perceived health status, and chronic disease were identified as factors influencing outpatient frequency for medical aid beneficiaries. These factors accounted for 11.2% of explanation (p < .001). For health insurance subscribers, factors affecting the length of hospitalization were gender, public pension status, place of residence, administrative district, economic activity, income level, perceived health status, and disability status. These factors accounted for 7.2% of explanation (p < .001). While, factors affecting the length of hospitalization for medical aid beneficiaries were accounted for by 3.4% (p < .001). Gender and perceived health status were identified as factors influencing the length of hospitalization of medical aid beneficiaries. Conclusions There were differences between medical aid beneficiaries and health insurance subscribers in health care use and influencing factors. Future management programs should take into consideration the specific factors that influence the use of health care services in health insurance subscribers and medical aid beneficiaries.